2020
DOI: 10.3390/cells9081893
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Stem Cell Systems to Explore Pathogen-Related Neurodevelopmental and Neurodegenerative Disorders

Abstract: Building and functioning of the human brain requires the precise orchestration and execution of myriad molecular and cellular processes, across a multitude of cell types and over an extended period of time. Dysregulation of these processes affects structure and function of the brain and can lead to neurodevelopmental, neurological, or psychiatric disorders. Multiple environmental stimuli affect neural stem cells (NSCs) at several levels, thus impairing the normal human neurodevelopmental program. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 228 publications
(306 reference statements)
0
15
0
Order By: Relevance
“…Their loss results in diseases such as spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (SLA) [ 2 , 3 ]. At present, pluripotent stem cells (PSCs) represent the most promising tool for the generation of large populations of human neural stem cells, committed progenitors and neurons in vitro, and for the establishment of patient-specific neuronal disease models [ 4 , 5 , 6 ]. Various methods have been developed for MNs production from PSCs, both of embryonic and somatic origin, generated by means of reprogramming techniques [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their loss results in diseases such as spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (SLA) [ 2 , 3 ]. At present, pluripotent stem cells (PSCs) represent the most promising tool for the generation of large populations of human neural stem cells, committed progenitors and neurons in vitro, and for the establishment of patient-specific neuronal disease models [ 4 , 5 , 6 ]. Various methods have been developed for MNs production from PSCs, both of embryonic and somatic origin, generated by means of reprogramming techniques [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is clear that the age of the host and the maturation of the NSCs are key variables in how viruses impact NSCs. TORCH pathogens [toxoplasmosis, other pathogens (e.g., syphilis, parvovirus), rubella, CMV, HSV], which are associated with congenital infections of the fetus or newborn, can cause catastrophic dysregulation and depletion of NSCs, contributing to a long-term loss of both neural progenitors and new neurons associated with microcephaly (see [ 107 ] for a comprehensive review). In a model of adult WNV infection, cytokine-mediated inhibition of hippocampal neurogenesis is associated with memory impairments, even though the number of NSCs remained stable [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The syncytiotrophoblast cells, which form the fetal part of placental barrier, are permissive to viral infection and replication in the first and second trimester ( Fisher et al, 2000 ). This may lead to viral infection of multiple cell types within the embryo, including NSCs ( Baggiani et al, 2020 ). Infection of murine embryos with murine CMV showed that ventricular and subventricular zones are the most affected ( Tsutsui et al, 2005 ).…”
Section: Viral Infections With Vertical Transmission From Mother To Fetusmentioning
confidence: 99%